The Effectiveness of Using Movie In Descriptive Style Speaking - Nur Hasibin; Wageyono Wageyono; Dimas Priagung Banar Syahputra (Darussalam English Journal, 2022)
The objective of the research is to prove whether using movies differentiates students' achievement in descriptive style speaking between students who are taught using movies and students who are taught using non-movies. The subject of this research was the students of seventh grade in classes VII B and VII C. The number of the subject was forty-four. The design of the research was used as experimental research. After doing the treatments, the researcher gave a post-test to both classes with the same instrument. After the data had been collected by test, it was found that the pre-test average of the experimental class was 62.27, and the control class was 61.82. While the post-test average of the experimental class was 72.73 and the control class was 66.14. The obtained t-test was 2.454, whereas the t-table was 1.68 for a = 5%. The t-test score was higher than the t-table (2.454 > 1.67). It meant that Ha was accepted while Ho was rejected. T-test score was higher than the t-table, hence movie was effective in improving students’ speaking ability in the seventh grade of SMP Negeri 1 Singojuruh in the academic year 2020/2021.